Electrochemical Properties of Nanoceria - Ali, Atif (My University, 2021)
The purpose of the study was to synthesize and examine the electrochemical properties of ceria (CeO2) nanoparticles and ceria-reduced graphene oxide (CeO2-RGO) nanocomposites. The synthesis of ceria nanoparticles and ceria-reduced graphene oxide (CeO2-RGO) nanocomposites were successfully carried out by using hydroxide mediated and sonochemical methods, respectively. The formation of ceria nanoparticles and ceria-reduced graphene oxide (CeO2-RGO) nanocomposites were confirmed by using characterization techniques such as UV-visible spectroscopy, Fourier-transform infrared (FTIR) spectroscopy, Raman spectroscopy and X-ray diffraction (XRD) techniques. The electrocatalytic reduction of oxygen, super capacitive behaviour of nanoceria and electrocatalytic oxidation of methanol by using nanoceria with cyclic voltammetry (CV) and rotating ring disc electrode (RRDE) techniques were analysed. The high oxidation peak current was observed with ceria nanoparticles coated on glassy carbon (GC) electrode in the electrooxidation of methanol in alkaline media. The electrocatalytic reduction of oxygen was successfully carried out with ceria-reduced graphene oxide (CeO2-RGO) nanocomposites coated on the glassy carbon (GC) and gold (Au) electrodes. The electrochemical reduction of para-nitrophenol was successfully done by ceria nanoparticles coated on glassy carbon (GC) electrode in aqueous solution. The ceria-reduced graphene oxide (CeO2-RGO) nanocomposites can enhance the electrocatalytic activity by inducing the synergistic effect. It can also have a great impact on the utilization of ceria-reduced graphene oxide (CeO2-RGO) nanocomposites in the electrochemical devices.